Left heart bypass in the surgery of aortic coarctation in children. Issue 12 (December 1988) - Buckels, N J; Willetts, R G; Roberts, K D
Abstract : Of 47 children over the age of 1 year who underwent repair of aortic coarctation during 1978-85, 22 had the operation performed with left heart bypass because the distal aortic pressure was below 50 mm Hg after the initial application of the arterial clamps. One further child had an elective left heart bypass. Satisfactory distal perfusion was achieved in all 23 patients. There were no deaths related to the use of left heart bypass but three complications occurred. One child had a mild transient hemiparesis on the ninth postoperative day and two had a pericardial effusion.